Self-assembling peptides-based nano-cargos for targeted chemotherapy and immunotherapy of tumors: recent developments, challenges, and future perspectives - Xue-Jun Wang; Jian Cheng; Le-Yi Zhang; Jun-Gang Zhang (Taylor & Francis Group, 2022)
Self-assembling peptides (SAPs) have enormous potential in medical and biological applications, particularly noninvasive tumor therapy. SAPs self-assembly is governed by multiple non-covalent interactions and results in the formation of a variety of morphological features. SAPs can be assembled in a variety of ways, including chemical conjugation and physical encapsulation, to incorporate multiple bioactive motifs. Peptide-based nanomaterials are used for chemotherapy, delivery vehicles, immunotherapy, and noninvasive tumor therapies (e.g. photodynamic therapy) by employing the self-assembling properties of peptides. The recent increase of SAPs is almost entirely due to their excellent biocompatibility, responsiveness toward tumor microenvironment, multivalency, and structural versatility. Synergistic therapy is a more effective and powerful approach to treat the tumor. Notably, SAPs can be used to subtly combine various treatments. Importantly, SAPs are capable of subtly making the combination of various treatments. This review describes mechanisms of peptides self-assemble into various structures and their biomedical applications with a focus on possible treatments.